The Safety of Urban Areas in Bosnia and Herzegovina in the Context of the Theory of Left Realism - Elezović, Vanja (Kriminalističke teme, 2015)
Reason(s) for writing and research problem(s): Violence and criminal activity are social problems that affect every society, and with it draw substantial media attention. Bosnia and Herzegovina are not excluded from this topic, and in fact is highlighted in the greater urban areas. Aims of the paper (scientific and/or social): The aim of the study was to review the current security situation on the issue of crime in Bosnia and Herzegovina, from the perspective of problems affecting the transitional state. Methodology/Design: In this paper we analyzed the safety of urban areas in Bosnia and Herzegovina through the prism of the theory of left realism, which can explain the current situation of bh society on a significant level. Comparative analyzes of data from different studies in Bosnia and Herzegovina and the world, in terms of indicators of social crisis that directly affect the growth of characteristic types of offenses such as those in the field of organized crime, corruption and violence by juveniles. Attention is mainly given to the situation in Sarajevo. Research/paper limitations: Limitations in this study relate primarily through consideration of the problem in a purely socio-economic framework, where other factors that influence the state of crime and safety in general are ignored. Results/Findings: Left realism insists on social inequalities as one of the main generators of crime, and in this paper of such a thesis is supported by a number of socio-economic indicators. So, it is a global atmosphere generated by the community in a way that people, regardless of their economic status, desire for the way of life of those who are wealthier. General conclusion: The security situation in Bosnia and Herzegovina is expressed in the general depression caused by the economic crisis, and all its side effects, which in the post-conflict and transitional state lead to relative deprivation in one part of the population, which entails greater number of criminal activities directed to the change of their own economic and social status. Research/paper validity: This study points to the need of introducing and implementing targeted economic measures in terms of prevention, and greater sensitivity in society for the most vulnerable, marginalized and discriminated groups.